18F-PSMA-1007 versus 18F-FDG PET/CT in the detection of hepatocellular carcinoma - Mei, Xiaoli; Li, Yanpeng; Xu, Shasha; Shang, Xiaoping; Cheng, Bing; Niu, Xiaobo; Liu, Xiaoting; Liu, Yan; Cheng, Xinya; Han, Xingmin; Wang, Ruihua (Frontiers in Oncology, 2025)
BackgroundProstate-specific membrane antigen (PSMA) is expressed in hepatocellular carcinoma (HCC). Recently, 18F-PSMA-1007 has been used for tumor imaging in positron emission tomography/computed tomography (PET/CT). This study aimed to compare the diagnostic performances of 18F-PSMA-1007 PET/CT and 18F-FDG PET/CT in HCC, and to assess factors associated with the sensitivity of 18F-PSMA-1007 PET/CT in detecting HCC and intrahepatic tumor lesions.Materials and MethodsForty-four patients with suspected HCC undergoing both 18F-FDG and 18F-PSMA-1007 PET/CT were prospectively enrolled. Two experienced nuclear medicine physicians independently interpreted imaging results. The mean standardized uptake values (SUVmean) were measured in the intrahepatic lesions (T), liver background (L), abdominal aorta (A), and right medial gluteal muscle (M), respectively. The tumor-to-background ratio (T/L, T/A, T/M) was then calculated as the SUVmean of the intrahepatic lesion (T) divided by the SUVmean of the background regions (L, A, M).ResultsSixty-two intrahepatic lesions in 41 patients with HCC were finally involved in the statistical analysis. 18F-PSMA-1007 PET/CT demonstrated higher sensitivity than 18F-FDG PET/CT in detecting HCC patients (85.4% vs. 61.0%, P = 0.041), particularly in identifying well- or moderately differentiated HCC patients (92.9% vs. 14.3%, P = 0.003). 18F-PSMA-1007 PET/CT showed a higher sensitivity than 18F-FDG PET/CT in detecting intrahepatic HCC lesions (82.3% vs. 50.0%, P = 0.001), including in small (≤ 2 cm in diameter; 62.5% vs. 25.0%, P = 0.049) and well- or moderately differentiated (88.9% vs. 14.8%, P < 0.001) lesions. The sensitivity of 18F-PSMA-1007 PET/CT was associated with tumor size (P = 0.005). The SUVmean values for the intrahepatic lesions (T) and liver background (L) from 18F-PSMA-1007 PET/CT were significantly higher compared with those from 18F-FDG PET/CT (both P < 0.001). Background uptake in the abdominal aorta (A) and right medial gluteal muscle (M) for 18F-PSMA-1007 was significantly lower than that for 18F-FDG (both P < 0.001). T/L, T/A and T/M values from 18F-PSMA-1007 were significantly higher than those from 18F-FDG PET/CT (all P < 0.001).Conclusions18F-PSMA-1007 PET/CT exhibits higher sensitivity than 18F-FDG PET/CT for detecting HCC and has lower background uptake in blood and muscle tissues. The sensitivity of 18F-PSMA-1007 is correlated mainly with tumor size.